Hypoxia/reoxygenation-induced myocardial lesions in newborn piglets are related to interindividual variability and not to oxygen concentration - Armando Faa; Nicoletta Iacovidou; Theodoros Xanthos; Annalisa Locci; Pietro Pampaloni; Filippia Aroni; Apostolos Papalois; Gavino Faa; Vassilios Fanos (Clinics, 2012)
OBJECTIVE: Evaluation of myocardial histological changes in an experimental animal model of neonatal hypoxiareoxygenation. METHODS: Normocapnic hypoxia was induced in 40 male Landrace/Large White piglets. Reoxygenation was initiated when the animals developed bradycardia (HR <60 beats/min) or severe hypotension (MAP <15 mmHg). The animals were divided into four groups based on the oxygen (O2) concentration used for reoxygenation; groups 1, 2, 3, and 4 received 18%, 21%, 40%, and 100% O2, respectively. The animals were further classified into five groups based on the time required for reoxygenation: A: fast recovery (<15 min); B: medium recovery (15-45 min); C: slow recovery (45-90 min); D: very slow recovery (>90 min), and E: nine deceased piglets. RESULTS: Histology revealed changes in all heart specimens. Interstitial edema, a wavy arrangement, hypereosinophilia and coagulative necrosis of cardiomyocytes were observed frequently. No differences in the incidence of changes were observed among groups 1-4, whereas marked differences regarding the frequency and the degree of changes were found among groups A-E. Coagulative necrosis was correlated with increased recovery time: this condition was detected post-asphyxia in 14%, 57%, and 100% of piglets with fast, medium, and slow or very slow recovery rates, respectively. CONCLUSIONS: The significant myocardial histological changes observed suggest that this experimental model might be a reliable model for investigating human neonatal cardiac hypoxia-related injury. No correlation was observed between the severity of histological changes and the fiO2 used during reoxygenation. Severe myocardial changes correlated strictly with recovery time, suggesting an unreported individual susceptibility of myocardiocytes to hypoxia, possibly leading to death after the typical time-sequence of events.